"Canones Eusebiani" w Biblii Płockiej z XII wieku - Misiarczyk, Leszek (Vox Patrum, 2010)
The article present the famous canons of Eusebius transmitted in medival version of the Bible of Plock (Poland). The Author hopes that publication of it will help scholars to develope a comparative studies between different manuscripts of medival Europe in order to conclude if there were one or more its versions in Middle Ages. Canons in so called “Bible of Plock” are slightly different from the version we can find in the internet (www.tertulian.org/fathers/eusebius_canon_ tables_01.html) but these differences are caused rather by a copist’s errors and don’t prove at all that in medival Poland or Europe there were in use a different canon versions. We need further comparative studies in this aerea and only afther these there will be possible to draw final conclusions.